2006
DOI: 10.4067/s0034-98872006000900008
|View full text |Cite
|
Sign up to set email alerts
|

Comportamiento clínico de los tumores cardíacos desde el feto hasta el adulto: serie multicéntrica de 38 pacientes

Abstract: Background: Cardiac tumors are very uncommon at all ages. There are important clinical differences between children and adults in the behavior (Rev Méd Chile 2006; 134: 1135-45).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 44 publications
0
8
0
4
Order By: Relevance
“…Thus, complete resolution was observed in 20 out of 24 rhabdomyomas studied in a 20-year follow-up period since the diagnosis made in infants up to 8 months old according to Smythe et al 3 , and in 31 out of 33 cases studied by Bosi et al 2 . Regression is observed up to the age of 5 to 6 years 6,7 . This fact makes the indication of surgical resection of these tumors unnecessary, except in life-threatening situations, as in the case of inflow tract obstruction and, mainly, ventricular outflow tract obstruction 8,9 .…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Thus, complete resolution was observed in 20 out of 24 rhabdomyomas studied in a 20-year follow-up period since the diagnosis made in infants up to 8 months old according to Smythe et al 3 , and in 31 out of 33 cases studied by Bosi et al 2 . Regression is observed up to the age of 5 to 6 years 6,7 . This fact makes the indication of surgical resection of these tumors unnecessary, except in life-threatening situations, as in the case of inflow tract obstruction and, mainly, ventricular outflow tract obstruction 8,9 .…”
Section: Discussionmentioning
confidence: 91%
“…As such, surgical resection of rhabdomyoma was necessary in only 9 out of 56 of these tumors according to Beghetti ; and in 1 out of 9 cases described by Smythe et al 3 . It has been observed that most of the obstructive rhabdomyomas found in neonates and infants are also subject to regression, and this makes the surgical resection of these tumors necessary only under life-threatening conditions [7][8][9][10] . However, the regression of these tumors is hard to understand, especially in the case of those located in fibrous regions of the heart, as for example in heart valves, as occurred in the unusual case reported here.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations